Rare Appendicitis-Like Syndrome: The Case of the Obstructing Broccoli - Stephen Jones; Patrick Narh-Martey; Mitun Patel; Amanpreet Dhaliwal; Jessica Persson; Denis Orr (Case Reports in Medicine)
The diagnosis of acute appendicitis can be somewhat obscure in a patient that presents with right lower quadrant abdominal pain. The advancement and ease of imaging have made CT scanning readily available in the emergency department. Management can be challenging when the patient has a high likelihood of appendicitis based on clinical suspicion and negative CT scan. The purpose of this case report is to demonstrate how an obstructing bezoar caused an appendicitis-like syndrome in a patient with negative CT scan and clinical diagnosis of acute appendicitis. This case report will discuss the appendicitis-like syndrome of an obstructing bezoar and an approach at management.